2001
DOI: 10.1161/hy1001.092652
|View full text |Cite|
|
Sign up to set email alerts
|

Localization of the Endothelin System in Aldosterone-Producing Adenomas

Abstract: Abstract-Endothelin-1 (ET-1) could play a role in the regulation of aldosterone secretion of the human adrenal gland. The presence of the endothelin-converting enzyme 1 (ECE-1) and ET-1 suggests that there is a local ET system in the adrenal cortex, but the in situ synthesis of ET-1 remains to be confirmed. The cellular distribution of the whole ET system was evaluated in 20 cases of aldosterone-producing adenomas. Polymerase chain reaction studies gave strong signals for ECE-1 mRNA and the mRNAs for endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Gene expression of the complete endothelin system was confirmed by microarray analysis, at levels equivalent to those of normal adrenal (178). In situ hybridization experiments have localized prepro-ET-1, ECE, and ETA and ETB receptor mRNAs in vascular structures (177). They have also revealed the presence of ECE and ETA receptor transcripts in steroidogenic adenoma cells (177).…”
Section: Factorsmentioning
confidence: 82%
See 2 more Smart Citations
“…Gene expression of the complete endothelin system was confirmed by microarray analysis, at levels equivalent to those of normal adrenal (178). In situ hybridization experiments have localized prepro-ET-1, ECE, and ETA and ETB receptor mRNAs in vascular structures (177). They have also revealed the presence of ECE and ETA receptor transcripts in steroidogenic adenoma cells (177).…”
Section: Factorsmentioning
confidence: 82%
“…The occurrence and role of endothelin system in the control of steroidogenesis have been extensively investigated in adrenal lesions associated with hyperaldosteronism. Expression of genes encoding prepro-ET-1, ECE-1, and ETA and ETB receptors has been detected in aldosterone-producing adenomas by PCR (177). Gene expression of the complete endothelin system was confirmed by microarray analysis, at levels equivalent to those of normal adrenal (178).…”
Section: Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Une très forte expression a été observée dans la surrénale [6]. La pré-sence d'ET-1 dans les structures vasculaires suggère une action autocrine et/ou paracrine sur le contrôle du flux sanguin dans la surrénale [13]. Les concentrations extrêmement élevées d'ECE-1 font penser que d'autres substrats que la big ET-1 sont clivés.…”
Section: Expression Et Modulation Du Système Endothélineunclassified
“…Recent studies have also shown that aldosterone can, in turn, upregulate ET-1 expression (13)(14)(15). Since normal adrenal tissue and adrenal adenomas express components of the ET system (16)(17)(18), a positive feedback loop between ETs and aldosterone may be hypothesized. Moreover, any ET spillover from the adrenal gland may have pathophysiological and diagnostic implications.…”
Section: Introductionmentioning
confidence: 99%